Texture in food : volume 1: Semi-solid foods - McKenna, Brian M. (Woodhead publishing in food science and technology, 2003)
Understanding and controlling the texture of semi-solid foods such as yoghurt and ice cream is a complex process. With a distinguished international team of contributors, this important collection summarises some of the most significant research in this area